2010
DOI: 10.1002/humu.21284
|View full text |Cite
|
Sign up to set email alerts
|

Structures and molecular mechanisms for common 15q13.3 microduplications involving CHRNA7: benign or pathological?

Abstract: We have investigated four ~1.6-Mb microduplications and 55 smaller 350–680-kb microduplications at 15q13.2–q13.3 involving the CHRNA7 gene that were detected by clinical microarray analysis. Applying high-resolution array-CGH, we mapped all 118 chromosomal breakpoints of these microduplications. We also sequenced 26 small microduplication breakpoints that were clustering at hotspots of nonallelic homologous recombination (NAHR). All four large microduplications likely arose by NAHR between BP4 and BP5 LCRs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
161
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(168 citation statements)
references
References 47 publications
7
161
0
Order By: Relevance
“…21 ASDs have been reported in 4/11 patients with small CHRNA7 duplications referred for chromosomal microarray analysis; however, its pathogenicity remains controversial. 22,23 Recently, Williams et al 24 reported association of the CHRNA7 duplication with attention-deficit hyperactivity disorder. Interestingly, in contrast to patient 4, his brother, who has the SNX19 deletion but not the CHRNA7 duplication, does not present problems with concentration.…”
Section: Discussionmentioning
confidence: 99%
“…21 ASDs have been reported in 4/11 patients with small CHRNA7 duplications referred for chromosomal microarray analysis; however, its pathogenicity remains controversial. 22,23 Recently, Williams et al 24 reported association of the CHRNA7 duplication with attention-deficit hyperactivity disorder. Interestingly, in contrast to patient 4, his brother, who has the SNX19 deletion but not the CHRNA7 duplication, does not present problems with concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, at least six classes of microduplications, varying in size from 350 kb to 1.6 Mb, were shown to arise involving pre-existing heterogeneous inverted BP4 and BP5 chromosomes. 7 Here we describe a non-recurrent triplication of 650.4 kb, for which the breakpoint junctions do not involve LCRs (Figure 3b), implicating an alternate underlying mechanism of formation. Its molecular characterization enabled us to experimentally classify it as type II or DUP-TRP/INV-DUP, likely generated by a replication-based mechanism.…”
Section: Discussionmentioning
confidence: 67%
“…Although deletions of CHRNA7 cause ID and neuropsychiatric phenotypes with relatively high penetrance, 3,4,6 the pathogenicity of CHRNA7 duplications remains unclear, given its high prevalence in the general population with multiple individuals that are clinically unaffected. 7 Therefore, it has been uncertain whether CHRNA7 is a dosage-sensitive gene with penetrant clinical phenotypes for both deletions and duplications. In this report, the family members harboring the triplication are affected with cognitive abilities in the borderline intellectual functioning range, and various degrees of neuropsychiatric pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By now, several studies have demonstrated that genetic variants in CHRNA7 were associated with various human diseases and traits, such as the associations between CNVs in CHRNA7 and various neurological disorders. [35][36][37][38] In addition, one study conducted in African and European Americans showed that one SNP of CHRNA7 was associated with nicotine dependence, 27 suggesting that the SNPs of CHRNA7 might show association with smoking-related diseases. Yet, till now, no published studies including genome-wide association studies (GWASs) have reported a significant association between CHRNA7 SNPs and the risk of smoking-related diseases, and this Figure 2 Path model for mediating effect of COPD on association between the CNV-3956 and lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%